FAMILY SUPPORT RELATED TO QUALITY OF LIVING ELDERLY WITH DEMENSIA - Wardani, Elia Domas Ayu; Retnaningsih, Dwi; Wulandari, Priharyanti (Universitas Widya Husada, 2020)
One of the many disease problems that arise in the elderly due to aging is dementia. Elderly people who experience dementia will gradually experience cognitive weakness. Family support is important for older people with dementia to improve quality of life. With the support of families in the elderly who experience dementia, the elderly lead a more vibrant and confident life. This study aims to determine the relationship of family support with the quality of life of the elderly who experience dementia. This research was non-experimental quantitative research with the correlational method, cross sectional approach. Respondents of 100 elderly who have dementia, the study was conducted in Margosari Village, Limbangan District with stratified random sampling technique based on inclusion and exclusion criteria. Using a questionnaire instrument. Processing data using Spearman rank statistics, with SPSS 22. The results of family support with the quality of life of the elderly who experience dementia obtained p value of 0.046 < 0,05. There was correlation between family support with the quality of life of the elderly who suffer from dementia.